2014
DOI: 10.1007/s10750-014-2019-x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial abundance patterns along a transparency gradient suggest a weak coupling between heterotrophic bacteria and flagellates in eutrophic shallow Pampean lakes

Abstract: The aim of this work was to study the components of the microbial food web and the degree of coupling between heterotrophic bacteria (HB) and heterotrophic flagellates (HF) in different shallow lakes of the Pampa Plain over a wide range of water transparency and nutrient levels. We hypothesized that not all microorganisms (i.e., HB, HF) equally increase with nutrient levels, thus, resulting in a weaker degree of coupling between HB and HF in more eutrophic waters. During the spring-summer 2009-2011, we sampled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 82 publications
2
16
0
1
Order By: Relevance
“…Regarding the spatial presence of the different zOTUs, each Pampean shallow lake was represented by a particular assemblage associated with local environmental factors. These results lend support to previous evidence about the importance of underwater light conditions and the availability of nutrients in governing freshwater picocyanobacterial distribution (35,(64)(65)(66)(67)(68).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Regarding the spatial presence of the different zOTUs, each Pampean shallow lake was represented by a particular assemblage associated with local environmental factors. These results lend support to previous evidence about the importance of underwater light conditions and the availability of nutrients in governing freshwater picocyanobacterial distribution (35,(64)(65)(66)(67)(68).…”
Section: Discussionsupporting
confidence: 89%
“…(ii) Eight freshwater samples were taken from four hypertrophic shallow lakes (Table S11) of the Salado River floodplain basin, located in the Pampa plain in Argentina (35°41=S, 59°35=W) (22,68). The samples were selected in order to cover spatial and temporal variation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At first, we considered all data we gathered from the literature in our analyses. However, some of the studies performed in highly eutrophic environments have found extreme values of HB and HNF abundance, never reported before on the literature (i.e., Fermani et al, 2013 , 2015 ). As we did not found any equivalent conditions in the tropical dataset, and since we noticed that the data from those studies were outliers, we decided to disregard those values from all our analyses.…”
Section: Resultsmentioning
confidence: 70%
“…Croatia (Šolić et al 2010), and in many eutrophic lakes (Wieltschnig et al 2001, Zingel et al 2007, Fermani et al 2014. The weak coupling between HNF and bacteria results in most cases from the strong top-down control of ciliates on HNF.…”
Section: Eutrophication Effect On Carbon Transfer Among the Microbialmentioning
confidence: 99%